Pemenuhan Hak Kesehatan Bagi Penyandang Disabilitas Sebagai Upaya Perlindungan Sosial - Nurika Falah Ilmania; Nofi Sri Utami (Fakultas Hukum Universitas Islam Malang, 2023)
This paper aims to find out the fulfillment of the right to health for persons with disabilities based on Law Number 36 of 2009 concerning Health and Law Number 8 of 2016 concerning Persons with Disabilities. This paper uses a normative juridical research method with a conceptual approach and a statutory approach. Persons with disabilities have the same right to obtain health services in a preventive, promotive, curative and rehabilitative manner aimed at maintaining a healthy and productive daily life. The state and society have an obligation to participate in efforts to fulfill the right to health as a form of social protection for persons with disabilities, especially in the health sector.